Interest, uptake, and feasibility trial of a real-life digital health intervention to improve lifestyle in Brazil - Raquel B De Boni; Jurema C Mota; Michael Duncan; Leonardo Linconl; Giovanna Lucieri Alonso Costa; Sofia Pimentel; Kamila P Sales; Fabiana Gaspar; Fernanda Adaes; Felipe B Schuch; Vicent Balanzá-Martinez; Flavio Kapczinski; et al. (Digital Health)
Objective Promoting healthy lifestyle behaviors is essential for preventing and managing chronic and mental health conditions. This study aims to present a digital health platform accessible via PC or smartphone, VIVA! , designed to foster lifestyle change among the Brazilian population. It evaluates interest, uptake, acceptability, usability, adherence, and retention over 12 weeks. Methods A fully online feasibility trial was conducted from April to December 2023. Participants were adults who lived in Rio de Janeiro and reported using the Brazilian Public Health System. Interest in VIVA! and uptake were assessed via recruitment metrics. Acceptability and usability were measured using the Mobile App Rating Scale (MARS). Adherence was calculated as the percentage of completed challenges over 12 weeks, and retention was tracked at 4, 8, and 12 weeks. Results Of 3812 individuals reached, 27.2% expressed interest in the app, with an uptake rate of 65.4%. A total of 401 participants were enrolled, predominantly women (73.3%) with higher education (61.6%). MARS acceptability scores were 2.9 for quality and 3.5 for specificity. Usability scores averaged around 3, with aesthetics rated the highest. Retention at 12 weeks was 4.5%, and the average adherence rate was 11.2%. Conclusion The VIVA! attracted women and highly-educated individuals, but its effectiveness was constrained by high attrition. These findings highlight key challenges in DHI implementation, including the need for robust outreach, iterative improvements, and strategies to sustain engagement. Addressing digital access, literacy inequities, and strengthening regulations are critical for the future success and equity of DHIs in public health systems. Trial registration The trial was registered at the Brazilian Clinical Trials Registry (Registro Brasileiro de Ensaios Clínicos -REBEC)—number RBR-2ssyb6q.